Edukasi Dampak Media Sosial dan Pencegahan Perundungan di SMA Muhammadiyah 16 Jakarta - Indriani; Andriany, Anissa Rizky (Prisani Cendekia, 2023)
A number of cases of bullying among teenagers surfaced in public throughout 2023. Data from the Indonesian Child Protection Commission (KPAI) states that there has been an increase in cases of violence against children due to various things including the impact of distance learning (PJJ) during the COVID-19 period, the influence of online games and social media that display violent shows that are not child-friendly. Community service carried out at SMA Muhammadiyah 16 Jakarta aims to educate and provide understanding regarding bullying and the impact of social media. The service was carried out in the form of socialization and also direct practice of using social media for bullying prevention. After the training, 94.1% of participants knew what bullying meant and 88.2% of participants were committed to being actively involved in bullying prevention.